The Study of Khalawatiyah Tradition about the Barazanji - Rusdiah Rusdiah; Andi Hudriati; Rahmadani Rahmadani (Tamaddun Life, 2021)
The study aims (1) to know the benefits of the Barazanji carried out by the Khalawatiyah tradition of the people in Parangloe society, and (2) To know the message of Khalawatiyah tradition about the Barazanji for the Parangloe society. The research designed in this study was qualitative research. The data were processed based on observation, interviews, and documentation. The writer does interviews with informants. The informants that are used in this research are the society of Khalawatiyah’s tarekat for finding the benefits and the message of Khalawatiyah tradition about the Barazanji for the parangloe society. The writer’s findings indicated that the benefits of the Barazanji carried out by the Khalawatiyah tradition of the people in Parangloe society are the Barazanji as inner satisfaction, the barazanji as giving bless a ceremony, the Barazanji as indicted media, the Barazanji for getting a reward, and Brazanji gives information for people to know and preserve the life history of the prophet Muhammad saw. The finding also indicated that the message of Khalawatiyah tradition about the Barazanji for the Parangloe society is the first the people must know the personality of the prophet Muhammad saw and hope to emulate all of about prophet Muhammad saw and the second people always sent shalawat to Muhammad saw.